Studies on heterosis for seed yield and its component traits in castor (Ricinus communis L.) hybrids suitable for Odisha state: STUDIES ON HETEROSIS FOR SEED YIELD AND ITS COMPONENTS IN CASTOR HYBRIDS FOR ODISHA - S K MOHANTY; P N JAGADEV; C LAVANYA (Journal of Oilseeds Research, 2021)
The experimental material consisted of 40 entries which included two pistillate lines (DPC-23 and M-571) and 12 monoecious lines (DCS-64, DCS-86, DCS-102, DCS-105, DCS-107, DCS-108, DCS-109, DCS-110, DCS-112, DCS-118, DCS-119, DCS-123), their resultant 24 hybrids developed through a line x tester mating design and two check hybrids (DCH-177 and DCH-519). These entries were tested in a randomized block design with three replications at AICRP centre on Castor, Bhawanipatna, Odisha over three years (2014-15 to 2016-17) during kharif season. Considering per se performance of hybrids, eleven hybrids recorded higher seed yield per plant than the check hybrid DCH-177 of which four hybrids viz., M-571 x DCS-110 (102.8 g/plant), M-571 x DCS-112 (100.6 g/plant), M-571 x DCS-105 (93.8 g/plant) and DPC-23 x DCS-110 (93.4g/plant) had high per se performance along with significant positive heterobeltiosis and standard heterosis for seed yield. The range of heterosis over better parent varied from -25 to 31.6%, while over standard check, it ranged from -30.1 to 24.3 %. The cross M-571 x DCS-110 depicted significantly the highest and positive heterobeltiosis (31.6%), standard heterosis (24.3 %) as well as the highest seed yield per plant (102.8g). Other cross combinations viz., M-571 x DCS-112, M-571 x DCS-105 and DPC-23 x DCS-110 were with significant and positive heterobeltiosis (28.7%, 20.1% and 24.0%, respectively), standard heterosis (21.6, 13.4 and 13.0%, respectively) and per se performance (100.6, 93.8 and 93.4 g/plant, respectively). The expression of heterotic response over better parents and standard check indicated the real superiority of the hybrids which could be exploited further through multilocational testing over different environments for judging their importance from the commercial point of view.